BEHAVIOR PERFORMANCE: A VALIDITY OF PERFORMANCE MANAGEMENT BEHAVIOR QUESTIONNAIRE (PBQ) INSTRUMENT - Sidharta Iwan (STMIK Mardira Indonesia, Bandung, 2018)
The objective of this study is to validate employee performance measurements in terms of behavioral aspects. The validated instrument was a Performance Management Behavior Questionnaire (PMBQ) instrument consisting of 27 statement items. The instrument statement consists of six dimensions, namely the Process of goal setting, Communication, Feedback, Coaching, Providing Consequences, and Establishing/monitoring performance expectations. Conducting a survey of retail sector employees in the city of Bandung, as many as 135 employees carried out using simple random sampling techniques. Testing instruments using Exploratory Factor Analysis (EFA). The results showed a valid and reliable psychometric analysis. The research implications can prove that the Performance Management Behavior Questionnaire (PMBQ) instrument can use as a reference for measuring employee performance in terms of aspects of consumer behavior. Keywords : instruments, employee behavior, employee performance.